ANALISIS EFEKTIVITAS PROGRAM KARTU TANI DI DESA CABAK, KECAMATAN JIKEN, KABUPATEN BLORA - Setiyo Budi; Sugihardjo Sugihardjo; Putri Permatasari (JSEP (Journal of Social and Agricultural Economics), 2021)
This study aims to analyze the effectiveness of the farmer card program in Cabak Village, Jiken District, Blora Regency. The research sample amounted to 79 farmers who were determined using the proportional random sampling method. The research data analysis method is descriptive quantitative. The effectiveness of the farmer card program is measured based on three indicators of measuring program effectiveness, namely program success, target success and program satisfaction. The results showed that the effectiveness of the farmer card program in Cabak Village was quite effective. Serious problems that occur in the implementation of farmer card in Cabak Village are the increase in fertilizer prices and the lack of subsidized fertilizers compared to farmers' needs.